Epilepsy in children: quality of life and disease control - Almomani, Miral A.; Almomani, Basima A.; Banikhaled, Roaa B.; Elayyan, Roa'a N.; Abu Abbas, Yumna H.; Al Thiabat, Hanan; Al-Qudah, Hashim (Frontiers in Neurology, 2025)
IntroductionChildhood epilepsy negatively affects health, quality of life (QoL), and character development.MethodsA cross-sectional online survey was conducted among pediatric epilepsy patients in Jordan. Candidates were identified through a hospital database. The shortened Quality of Life in Childhood Epilepsy Questionnaire (QOLCE-55) assessed QoL. Disease control was defined as seizure-free for 1 year. Clinical characteristics, QoL, disease control, and their determinants among pediatric epilepsy patients in Jordan were assessed.ResultsA total of 178 patients participated. The mean health-related QoL (HRQoL) score was 50.74 ± 22.54, highest in emotional wellbeing (60.75 ± 19.40) and lowest in physical functioning (44.75 ± 24.06). Higher HRQoL was significantly associated with older age at diagnosis (β = 1.668, P = 0.001), absence of comorbidities (β = −10.851, P = 0.006), fewer seizures annually (β = 7.572, P = 0.001), and use of fewer antiepileptic medications (β = −10.665, P = 0.002). Only 42.1% had controlled epilepsy. Disease control was associated with older age (OR = 1.134, 95% CI: 1.011–1.272, P = 0.032) and higher QoL (OR = 1.035, 95% CI: 1.014–1.057, P = 0.001). Uncontrolled seizures were linked to caregiver exhaustion (OR = 0.34, 95% CI: 0.155–0.743, P = 0.007) and polytherapy (OR = 0.397, 95% CI: 0.179–0.882, P = 0.023).ConclusionEpilepsy significantly reduces QoL in children. Better QoL and seizure control were linked to older age, absence of comorbidities, fewer seizures, and reduced medication use. Caregiver support and minimizing polytherapy may enhance both QoL and disease control.